Traumatic Middle Cerebral Artery Aneurysm Secondary to a Gunshot Wound. Issue 1 (11th January 2011) - Santos, Gonçalo; Lima, Tiago; Pereira, Sara; Machado, Egídio
ABSTRACT Traumatic intracranial aneurysms are rare lesions, accounting for less than 1% of all intracranial aneurysms. Formation of these lesions after a penetrating missile wound is very unusual, and diagnosis can be difficult due to the presence of associated lesions. In this article, we report a case of a woman who developed a middle cerebral artery aneurysm after a gunshot wound, and discuss potential pitfalls found during diagnostic work‐up.